Synergistic high-plasticity AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure and preparation method of AlCrFeNi as-cast multi-principal-element alloy

By optimizing the composition and preparation process of AlCrFeNi alloy, a cast multi-principal element alloy with nanoscale amplitude-modulated decomposition structure was prepared, which solved the problem of low room temperature plasticity and achieved a combination of high strength and high plasticity, making it suitable for aerospace and automotive manufacturing and other fields.

CN121006475APending Publication Date: 2025-11-25HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511281261.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing methods for preparing AlCrFeNi multi-principal-element alloys cannot achieve amplitude-modulated decomposition microstructures, resulting in low room-temperature plasticity and making them unsuitable for applications in aerospace and automotive manufacturing.

Method used

By optimizing the alloy composition to Al: 7~8 wt%, Cr: 16~21 wt%, Fe: 30~35 wt%, and Ni: 38~43 wt%, and controlling the elemental molar ratio of Fe+Cr to Ni+Al to be 0.96~0.97, a cast multi-principal element alloy with nanoscale amplitude-modulated decomposition structure was prepared by vacuum induction furnace melting and electromagnetic stirring.

Benefits of technology

Achieving a balance between high strength and high plasticity, the cast alloy exhibits 52% compressive strain and 26% elongation at room temperature, with yield strength and tensile strength of 1160 MPa and 1180 MPa, respectively. It maintains good performance at 800℃, has a high melting point and low density, and reduces material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121006475A_ABST
    Figure CN121006475A_ABST
Patent Text Reader

Abstract

The invention relates to a synergistic strong plasticity AlCrFeNi as-cast multi-principal-element alloy with an amplitude-modulated decomposition structure and a preparation method of the alloy, and belongs to the technical field of multi-principal-element alloy materials. In order to solve the problem that an existing AlCrFeNi multi-principal-element alloy preparation method cannot achieve amplitude-modulated decomposition so as to improve the room-temperature plasticity of the alloy, the invention provides a synergistic strong-plasticity AlCrFeNi as-cast multi-principal-element alloy with an amplitude-modulated decomposition structure, and the alloy comprises the following alloy components: 7-8 wt% of Al, 16-21 wt% of Cr, 30-35 wt% of Fe and 38-43 wt% of Ni. According to the AlCrFeNi multi-principal-element alloy and the preparation method thereof, the AlCrFeNi multi-principal-element alloy with a double-phase nanoscale fine amplitude-modulated decomposition structure is prepared through component optimization design, the alloy can achieve strong plasticity matching at the room temperature in a cast state through regulation and control over the microstructure, and meanwhile the alloy shows good performance stability and high-temperature bearing capacity in a high-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of multi-principal element alloy materials, and particularly relates to a synergistic high-strength and high-plasticity AlCrFeNi as-cast multi-principal element alloy with spinodal decomposition structure and a preparation method thereof. BACKGROUND

[0002] AlCrFeNi multi-principal element alloy (MPEA) has comprehensive properties such as low density and high strength, and has shown great application potential in high-end manufacturing fields such as aerospace and automobile manufacturing. Various AlCrFeNi multi-principal element alloys have been developed at home and abroad, but the matching problem of plasticity and strength has not been solved.

[0003] AlCrFeNi multi-principal element alloy can undergo various phase transitions when cooled from high-temperature liquid state. When rapidly cooled, the alloy undergoes non-equilibrium phase transition to form a metastable structure, and the elements are segregated to form a nanoscale L21 dispersed second phase, which effectively improves the yield strength. When the cooling rate decreases, the alloy tends to form a dual-phase dendritic structure, making the alloy have thermal stability. At a specific composition interval and critical cooling rate, the alloy will undergo spinodal decomposition, and the self-organized nanostructure can produce an additional strengthening effect through a coherent strain field. Spinodal decomposition is often accompanied by ordering transformation, making the alloy have a unique synergistic effect of high strength and high plasticity. At present, the existing technology has not successfully realized the spinodal decomposition structure in AlCrFeNi, and there is no report on solving the problem of low room temperature plasticity of the alloy system through nanoscale spinodal decomposition structure. SUMMARY

[0004] To solve the problem that the existing AlCrFeNi multi-principal element alloy preparation method cannot realize spinodal decomposition and thus improve the room temperature plasticity, the application provides a synergistic high-strength and high-plasticity AlCrFeNi as-cast multi-principal element alloy with spinodal decomposition structure and a preparation method thereof.

[0005] The technical scheme of the application is as follows:

[0006] A synergistic high-strength and high-plasticity AlCrFeNi as-cast multi-principal element alloy with spinodal decomposition structure contains the following alloy components: Al: 7-8 wt%, Cr: 16-21 wt%, Fe: 30-35 wt%, and Ni: 38-43 wt%, and the element molar ratio of Fe+Cr to Ni+Al is 0.96-0.97.

[0007] Further, the alloy contains the following alloy components: Al: 7.67 wt%, Cr: 18.66 wt%, Fe: 32.68 wt%, and Ni: 40.99 wt%.

[0008] The application discloses a preparation method of a synergistically strong plasticity AlCrFeNi as-cast multi-principal-component alloy with amplitude modulation decomposition organization, and steps are as follows:

[0009] Step one, the multi-principal-component alloy contains alloy components as follows: Al: 7-8 wt%, Cr: 16-21 wt%, Fe: 30-35 wt% and Ni: 38-43 wt%, and the element molar ratio of Fe+Cr to Ni+Al is 0.96-0.97; pure metals with a purity greater than 99.9% are selected as raw materials, the raw materials are weighed according to the proportion, and then are cleaned and dried, and then are put into a crucible and loaded into a vacuum induction furnace;

[0010] Step two, after the vacuum induction furnace is vacuumized, high-purity argon is filled to a certain gas pressure;

[0011] Step three, the metal raw materials are melted by induction heating, and uniform mixing is promoted by electromagnetic stirring, and the as-cast AlCrFeNi multi-principal-component alloy is obtained by pouring.

[0012] Further, the multi-principal-component alloy contains alloy components as follows: Al: 7.67 wt%, Cr: 18.66 wt%, Fe: 32.68 wt% and Ni: 40.99 wt%.

[0013] Further, the vacuum degree of step two is 10 -2 ~10 -3 Pa, and the gas pressure of the high-purity argon filled is 0.05-0.1 Mpa.

[0014] Further, the frequency of the induction heating of step three is 2-10 kHz, and the induction heating temperature is 1500 DEG C.

[0015] Further, the liquid alloy uniformly mixed in step three is first kept warm and placed for 5-15 min to make impurities precipitate, and then is poured.

[0016] The application has the following beneficial effects:

[0017] The application successfully develops the AlCrFeNi multi-principal-component alloy with a dual-phase nano-sized small amplitude modulation decomposition organization through component optimization design. The special organization is mainly formed due to accurate proportioning of alloy components. The application clarifies the key influence of Cr element content on formation of the amplitude modulation decomposition organization through thermodynamic calculation and first principle calculation, and determines the optimal component range. The nano-sized amplitude modulation structure has excellent interface coherent property, provides a unique strengthening mechanism for the alloy, and meanwhile retains good plastic deformation capacity. It is worth noting that the organization can be obtained in the as-cast state without additional heat treatment, greatly simplifies a production process flow and reduces manufacturing cost.

[0018] Thanks to the unique structure of the nanoscale amplitude-modulated decomposition microstructure, this alloy exhibits excellent strength-ductility matching at room temperature. Compression tests show that the as-cast alloy has a room temperature compressive strain as high as 52%, a yield strength of 1160 MPa, and a compressive strength of 3079 MPa; in tensile tests, the elongation reaches 26%, the yield strength is 793 MPa, and the tensile strength is 1180 MPa. These performance indicators break through the limitation of traditional AlCrFeNi alloys, which can only be tested for compression, and achieve true tensile performance testing capability. The fine two-phase structure formed by amplitude-modulated decomposition effectively hinders dislocation movement. The fit results of the work-hardening Ludwick model confirm that this alloy has strong work-hardening ability. At the same time, the moderate modulus difference allows dislocations to be absorbed or emitted at the phase boundaries, promoting the dispersion of strain localization regions and avoiding premature microcrack formation, thereby significantly improving macroscopic ductility. This perfect combination of high strength and high ductility makes this alloy more valuable for practical applications.

[0019] This alloy not only exhibits excellent performance at room temperature but also demonstrates good performance stability at high temperatures. At 800℃, the as-cast alloy retains a compressive strength of 437 MPa and a tensile strength of 276 MPa, showing good high-temperature load-bearing capacity. Furthermore, the alloy possesses a high melting point (1352℃) and low density (7.43 g / cm³), giving it a significant advantage in the field of lightweight high-temperature structural materials. Particularly noteworthy is that this alloy is completely free of expensive alloying elements such as Co, Cu, and Ti. Through optimized proportions of Al, Cr, Fe, and Ni, material costs are significantly reduced while maintaining excellent performance. This "low-cost, high-performance" characteristic, coupled with the ability to obtain an ideal microstructure using a general-purpose manufacturing process, makes this alloy a promising candidate for industrial applications in aerospace, energy equipment, and other fields. Attached Figure Description

[0020] Figure 1 As-cast AlCr 1.5 Fe2Ni 2.5 Photos of actual alloy ingots;

[0021] Figure 2 For Comparative Example 1, AlCr2Fe2Ni 2.5 Alloy and AlCr in Example 1 1.5 Fe2Ni 2.5 Free energy-composition relationship diagrams of alloys at different temperatures, (a) for AlCr2Fe2Ni 2.5 Alloy, (b) is AlCr 1.5 Fe2Ni 2.5 alloy.

[0022] Figure 3 As-cast AlCr 1.5 Fe2Ni2.5 XRD results of the alloy;

[0023] Figure 4 As-cast AlCr 1.5 Fe2Ni 2.5 Micrographs of the metallographic structure of the alloy, (a) is the metallographic structure, (b) is the SEM image;

[0024] Figure 5 As-cast AlCr 1.5 Fe2Ni 2.5 The surface scan elemental distribution diagrams of the alloy are shown in the following figures: (a) is the original diagram, (b) is Fe, (c) is Cr, (d) is Ni, and (e) is Al.

[0025] Figure 6 As-cast AlCr 1.5 Fe2Ni 2.5 Stress-strain curves of the alloy under room temperature compression.

[0026] Figure 7 As-cast AlCr 1.5 Fe2Ni 2.5 Stress-strain curves of the alloy under room temperature tensile testing;

[0027] Figure 8 As-cast AlCr 1.5 Fe2Ni 2.5 Stress-strain curves of alloys under high-temperature compression.

[0028] Figure 9 As-cast AlCr 1.5 Fe2Ni 2.5 Stress-strain curves of alloys under high-temperature tensile conditions. Detailed Implementation

[0029] The technical solution of the present invention will be further described below with reference to embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention. In the following embodiments, the process equipment or apparatus not specifically specified are all conventional equipment or apparatus in the art. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available; unless otherwise specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0030] Example 1

[0031] This embodiment provides a method for preparing an AlCrFeNi synergistically strong and ductile multi-principal element alloy with amplitude-modulated decomposition structure. The specific preparation steps are as follows:

[0032] Step 1: Select pure metals with a purity greater than 99.9% as raw materials according to the following multi-principal alloy composition: Al: 7~8 wt%, Cr: 16~21 wt%, Fe: 30~35 wt% and Ni: 38~43 wt%. Weigh the raw materials according to the proportion, clean and dry them, put them into a crucible and load them into a vacuum induction furnace.

[0033] Step 2: At the start of melting, turn on the mechanical pump. After 3 minutes, open the Roots valve to evacuate to 10°C. -3 Pa, fill with high-purity argon gas to 0.08 MPa;

[0034] Step 3: Induction heating at 10 kHz to 1500 ℃, electromagnetic stirring to promote uniform mixing, holding at this temperature for 15 minutes, and then casting to obtain a cast AlCrFeNi multi-principal element alloy ingot. The appearance is as follows: Figure 1 As shown in Table 1, the elemental content of the as-cast alloy was determined using a NexION 350X inductively coupled plasma optical emission spectrometer. The results are named AlCr. 1.5 Fe2Ni 2.5 alloy.

[0035] Table 1

[0036]

[0037] Comparative Example 1

[0038] This comparative example provides an AlCr2Fe2Ni 2.5 The alloy in this comparative example differs from that in Example 1 only in that the alloy in this comparative example is AlCr2Fe2Ni. 2.5 The alloy contains the following alloy composition: Al: 6.83 wt. / %, Cr: 25.56 wt. / %, Fe: 31.07 wt. / %, and Ni: 36.54 wt. / %.

[0039] Thermodynamic calculations were performed on the alloy compositions of Example 1 and the comparative example to analyze the thermodynamic conditions generated by amplitude modulation decomposition.

[0040] Using the Bragg-Williams model, considering both chemical interaction energy and elastic interaction energy, the Gibbs free energy calculation formula is shown in Equation 1. The AlCrFeNi alloy mainly consists of B2 and A2 phases, with Ni and Al enriched and Fe and Cr enriched, respectively. Therefore, a pseudo-binary method is used to approximate the alloy system, mainly considering the influence of two types of elemental composition: Fe and Cr are A-type atoms, and Ni and Al are B-type atoms. Due to the high content of the BCC phase, the alloy is simplified to a BCC structure.

[0041] (1)

[0042] The fourth term in the equation considers the contribution of the long-range elastic interaction energy to the Gibbs free energy in the system. Under the long-wavelength approximation, the long-range elastic interaction energy parameter can be simplified in the two-dimensional model as follows:

[0043] (2)

[0044] (3)

[0045] (4)

[0046] In the formula, h, k, and l are lattice indices. Let C be the component along the x and y directions in reciprocal space, Δ be the elastic anisotropy constant, and C be the component along the x and y directions. ij ε0 is the elastic constant of the alloy parent phase.

[0047] First, a model is constructed using a special quasirandom structure (SQS), and first-principles calculations are performed to obtain the elasticity constant C. 11 C 12 and C 44 Subsequently, curves showing the change of alloy free energy with composition at different temperatures were obtained, such as... Figure 2 As shown.

[0048] The AlCr2Fe2Ni2.5 alloy undergoes only a homogeneous transformation upon high-temperature cooling, with the liquid phase transforming into the A2 phase, ultimately exhibiting a dendritic biphase structure at room temperature, such as... Figure 2 As shown in (a). And AlCr 1.5 Fe2Ni 2.5 In contrast, the Gibbs free energy as a function of temperature is as follows: Figure 2 As shown in (b), the alloy undergoes different types of solid solution precipitation phase transformations at different temperatures. At high temperatures, the alloy tends to be disordered due to the significant contribution of mixing entropy to free energy, resulting in a continuous composition. As the temperature decreases, the phase transformation occurs as a heterogeneous nucleation transformation between the liquid phase and the disordered solid solution, resulting in amplitude modulation decomposition. When the temperature drops below the amplitude modulation decomposition temperature, the second phase in the alloy precipitates in the form of eutectoid or eutectic phase transformation, forming a multiphase coexistence structure. In the AlCrFeNi alloy, this corresponds to the spontaneous separation from the homogeneous solid solution into nanoscale coherent Al-Ni-rich and Cr-Fe-rich regions, i.e., A2 transforms into B2.

[0049] The fundamental reason for the significant differences in free energy curves and alloy microstructure is the change in Cr content. When the Cr content is low, the free energy-composition curve of the alloy exhibits a double-potential-well structure at a specific temperature (e.g., 1000℃) (i.e., the free energy curve has two local minima, and the intermediate region satisfies...). This morphology is a necessary thermodynamic condition for amplitude modulation decomposition. As the Cr content increases, the free energy curve gradually transforms into a single potential well. The double potential well structure disappears. At this point, the system enters the nucleation-growth region, and amplitude modulation decomposition cannot occur.

[0050] In the enthalpy of mixing of the four elements, Cr exhibits moderately negative or weakly positive enthalpies of mixing with other elements (such as Al and Ni), while the enthalpies of mixing with other elements are lower. Furthermore, Cr has the largest atomic radius among the four elements, and increasing its content significantly increases the difference in atomic size. High Cr content significantly increases the overall enthalpy of mixing of the system, disrupting the chemical interaction equilibrium required for amplitude modulation decomposition. The atomic radius of Cr differs significantly from that of Al and Ni; high Cr content exacerbates lattice distortion, leading to a significant increase in strain energy. This increase in strain energy shifts the free energy curve upwards overall and may eliminate… The region. The "high entropy effect" of multi-principal alloys helps stabilize the solid solution at low Cr content, but high Cr content can reduce configuration entropy due to Cr site preference, making the free energy curve tend to a simpler single potential well morphology.

[0051] Therefore, the design of Cr content in this invention is of great significance. When the Cr content is 16~21 wt. / %, and the elemental molar ratio of Fe+Cr to Ni+Al is 0.96~0.97, the as-cast alloy in this composition range at room temperature is expected to obtain an ideal amplitude decomposition structure, thereby obtaining a multi-principal element alloy with both strength and plasticity.

[0052] For the as-cast AlCr prepared in Example 1 1.5 Fe2Ni 2.5 The alloy was characterized by its microstructure and its properties were tested.

[0053] I. Phase analysis was performed using an Empyrean intelligent X-ray diffractometer with a diffraction angle range of 20-100°.

[0054] As-cast AlCr 1.5 Fe2Ni 2.5 The alloy is composed of Al, A2 and B2 phases, such as Figure 3 As shown, the A2 phase consists of a disordered [Fe, Cr] phase, the B2 phase consists of NiAl, and the A1 phase consists of (Fe, Al)(Ni, Cr). A single-phase peak line of the B2 phase appears at 2θ = 30.03 °, which can be distinguished from the A2 phase.

[0055] 2. The microstructure of the alloy was observed using an OM metallographic microscope and a SEM scanning electron microscope, followed by EDS (Energy Dispersive Spectrometer) elemental distribution analysis.

[0056] The sample surfaces were sanded with sandpaper in the order of 280#, 400#, 600#, and 1000#, respectively, followed by polishing and etching. The etching solution was prepared as 5 vol.% HF + 95 vol.% C2H5OH, and the etching time was 10-12 s.

[0057] like Figure 4 As shown, as-cast AlCr 1.5 Fe2Ni 2.5 The metallographic structure of the alloy consists of two phases of varying depths. The network structure observed in the metallographic analysis reveals interlocking, short, rod-shaped amplitude-modulated decomposition structures. Combined with... Figure 5 The EDS elemental distribution shows that the dark matrix is ​​mainly composed of Ni and Al, while the light-colored precipitates are Fe and Cr. Correspondingly, the XRD analysis results indicate that the dark phase is B2 and the light phase is A2. The alloy undergoes amplitude modulation decomposition, revealing two phases with the same structure but different compositions, which is beneficial for improving the alloy's plasticity.

[0058] III. Performance Testing.

[0059] As-cast AlCr prepared in Example 1 1.5 Fe2Ni 2.5 The alloy has a melting point of 1352℃; its density, determined using Archimedes' displacement method, is 7.43 g / cm³. 3 As-cast AlCr 1.5 Fe2Ni 2.5 The alloy has a microhardness of 335 kgf / mm. 2 .

[0060] IV. Perform room temperature compression test according to GB / T 7314-2017.

[0061] The sample size was Ф4×6 mm, the load was 500 kg, the loading rate was 2 mm / min, and the deformation was 50%.

[0062] As-cast AlCr prepared in Example 1 1.5 Fe2Ni 2.5 The engineering stress-strain curve of the alloy is as follows: Figure 6 As shown, the as-cast alloy has a compressive strain of 52%, a yield strength of 1160 MPa, and a compressive strength of 3079 MPa.

[0063] Due to AlCr 1.5 Fe2Ni 2.5 The work hardening of the alloy is relatively long, corresponding to the parabolic stage in the actual stress-strain curve. During this stage, the compressive strength gradually increases, playing a crucial role in strengthening the alloy. The Ludwik model is used to handle the work hardening behavior; the mathematical model is as follows:

[0064] (5)

[0065] In the formula, σ is the actual stress, ε is the actual strain, k is the strength coefficient, and n1 and n2 are coefficients that together form the work hardening index n, i.e., n = n1 + n2lnε.

[0066] Simplify by taking the logarithm of both sides of equation 5, as shown in equation 6:

[0067] (6)

[0068] For AlCr 1.5 Fe2Ni 2.5 The true stress-strain curves of the alloy were fitted to evaluate its work hardening properties. The Ludwik model was used for as-cast AlCr... 1.5 Fe2Ni 2.5 The alloy showed good fit, with a fit coefficient of 0.93. A larger n value indicates a stronger strain hardening effect, greater uniform deformation capability, and better deformation performance. For multi-principal element alloys, a larger n value is better during the plastic deformation stage. (As-cast AlCr) 1.5 Fe2Ni 2.5 The alloy maintains a consistently high n-value, exhibiting high work hardening properties and excellent deformation capacity.

[0069] 5. Perform room temperature tensile testing according to GB / T 228.1-2021, with a loading speed of 1 mm / min.

[0070] As-cast AlCr 1.5 Fe2Ni 2.5 The alloy has an elongation of 26%, a yield strength of 793 MPa, and a tensile strength of 1180 MPa. Its engineering stress-strain curve... Figure 7 It can be seen that the as-cast AlCr 1.5 Fe2Ni 2.5 The alloy exhibits excellent room temperature tensile properties with no necking elongation and uniform deformation during room temperature tensile testing, and the room temperature tensile test was successfully completed.

[0071] VI. Conduct high-temperature compression test according to GB / T 44030-2024.

[0072] The sample size was Ф4×6 mm, the heating rate was 15℃ / min, the holding time was 5 min, the loading rate was 2 mm / min, and the deformation was 50%. As-cast AlCr 1.5 Fe2Ni 2.5 The high-temperature compression properties of the alloy are shown in Table 2.

[0073] Table 2

[0074]

[0075] As shown in Table 2, none of the alloys fractured when the deformation reached 50%, and the compressive strain remained constant at approximately 47%. The alloy exhibited a significant difference in high-temperature compressive strength between 800℃ and 900℃, as shown in its engineering stress-strain curves. Figure 8 This is even more evident in AlCr. 1.5 Fe2Ni 2.5 The alloy maintains a high compressive strength of 368 MPa at 800℃. This strength decreases to 184 MPa at 900℃ and further to 123 MPa at 1000℃, which is attributed to the dissolution of the microstructure at high temperatures.

[0076] VII. High-temperature tensile tests were conducted according to GB / T 4338-2006, with a heating rate of 15℃ / min, a holding time of 5 min, and a loading rate of 1 mm / min. The tensile test results for this alloy at 800℃, 900℃, and 1000℃ are shown in Table 3, and the engineering stress-strain curves are as follows. Figure 9 As shown.

[0077] Table 3

[0078]

[0079] The tensile properties of the alloy at 800℃ differ significantly from those at 900℃ and 1000℃. This difference is... Figure 9 The difference is more pronounced in the middle. The alloy maintains high strength at 800℃, with a tensile strength of 276 MPa in the as-cast state. After 900℃, the strength decreases to 149 MPa, but the elongation increases significantly to 35%.

Claims

1. A synergistically strong and ductile AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure, characterized in that, It contains the following alloy composition: Al: 7~8 wt%, Cr: 16~21 wt%, Fe: 30~35 wt%, and Ni: 38~43 wt%, and the molar ratio of Fe+Cr to Ni+Al is 0.96~0.

97.

2. The synergistically strong and ductile AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure according to claim 1, characterized in that, It contains the following alloy composition: Al: 7.67 wt%, Cr: 18.66 wt%, Fe: 32.68 wt%, and Ni: 40.99 wt%.

3. A method for preparing a synergistically strong and ductile AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure, characterized in that, The steps are as follows: Step 1: The multi-principal element alloy contains the following alloy composition: Al: 7~8 wt%, Cr: 16~21 wt%, Fe: 30~35 wt%, and Ni: 38~43 wt%, and the elemental molar ratio of Fe+Cr to Ni+Al is 0.96~0.97; pure metals with a purity greater than 99.9% are selected as raw materials, the raw materials are weighed according to the proportion, cleaned and dried, placed in a crucible, and loaded into a vacuum induction furnace; Step 2: After the vacuum induction furnace is evacuated, it is filled with high-purity argon gas to a certain pressure. Step 3: Melt the various metal raw materials by induction heating, promote uniform mixing by electromagnetic stirring, and cast to obtain the as-cast AlCrFeNi multi-principal-element alloy.

4. The method for preparing a synergistically strong and ductile AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure according to claim 3, characterized in that, The multi-principal element alloy contains the following alloy composition: Al: 7.67 wt%, Cr: 18.66 wt%, Fe: 32.68 wt%, and Ni: 40.99 wt%.

5. The method for preparing a synergistically strong and ductile AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure according to claim 4, characterized in that, The vacuum level described in step two is 10. -2 ~10 -3 Pa, wherein the pressure of the high-purity argon gas is 0.05~0.1 MPa.

6. A method for preparing a synergistically strong and ductile AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure according to claim 4 or 5, characterized in that, The frequency of induction heating in step three is 2~10 kHz, and the induction heating temperature is 1500 ℃.

7. The method for preparing a synergistically strong and ductile AlCrFeNi as-cast multi-principal-element alloy with amplitude-modulated decomposition structure according to claim 6, characterized in that, Step 3: The uniformly mixed liquid alloy is first kept at a constant temperature for 5-15 minutes to allow impurities to settle before casting.

Citation Information

Patent Citations

  • High-toughness multilevel heterogeneous FeCrNiAl-based alloy material and preparation method thereof

    CN114807770A

  • Liquid lead bismuth corrosion resistant high-entropy alloy and preparation method thereof

    CN115627405A

  • Low-density high-strength plasticity FeCrNiAl series high-entropy alloy and preparation method thereof

    CN117587313A

  • High-strength and high-corrosion-resistance Fe-Cr-Ni-Al series high-entropy alloy and preparation method thereof

    CN117701971A

  • Novel light high-strength Al-Cr-Fe-Ni eutectic high-entropy alloy and preparation method thereof

    CN120485622A